Stress fractures: a review of 180 cases - Brukner, P.; Bradshaw, C.; Khan, K. M.; White, S.; Crossley, K. (Clinical Journal of Sport Medicine, 1996)
OBJECTIVE. To review the cases of stress fracture seen over a 2-year period at a sports medicine clinic. DESIGN. One hundred and eighty cases diagnosed as stress fractures on the basis of clinical picture and radiological evidence were reviewed. The following features of each stress fracture were noted: age, sex, site, sport/activity. SETTING. A sports medicine centre in Melbourne, Australia. PATIENTS. The average age was 21.8 years. Seventy eight of these stress fractures were seen in women, 102 in men. RESULTS. The most common sites of stress fractures were the metatarsal bones (n = 42), tibia (n = 36), fibula (n = 30), tarsal navicular (n = 26) and pars interarticularis (n = 17). The most common sport was track (n = 54). Other common sports activities were jogging/distance running (n = 35), dance (n = 32) and Australian football (n = 14). The distribution of sites of stress fractures varied from sport to sport. Among the track athletes (n = 54), navicular (n = 19), tibia (n = 14) and metatarsal (n = 9) were the most common stress fracture sites. The distance runners (n = 35) predominantly sustained tibia (n = 15), and fibula (n = 8) stress fractures, while metatarsal stress fractures (n = 18) were the most common among dancers. The distribution of sports varied with the site of the stress fracture. In the metatarsal stress fractures (n = 42), dance was the most common activity. Distance running (n = 15) and track (n = 14) were the most common sports in the group to have sustained tibia stress fractures (n = 36). Track athletes (n = 14) were particularly prevalent in the navicular stress fracture group (n = 26). CONCLUSION. The distribution of sites of stress fractures in this study shows some differences from previously published studies.